2010
DOI: 10.4293/108680810x12924466007926
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Cholecystectomy Conversion Rates Two Decades Later

Abstract: Male patients greater than 50 years of age and cases performed by low-volume surgeons were found to have a higher rate of conversion to open procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
61
1
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 27 publications
4
61
1
12
Order By: Relevance
“…9 In present study, 21 patients' (11.47%) operations were converted due to difficulties encountered intraoperatively which is higher than the conversion rate of patients found in other reports which is 5.9%, 12 due to difficult anatomy (6.55%) 8 due to the discovery of adhesions (4.37%) and one patient's operations were converted due to common bile duct injuries (0.54%). 12 Acute inflammation around Calot's triangle makes the tissue friable and difficult to grasp. Dissection in such conditions leads to excessive bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…9 In present study, 21 patients' (11.47%) operations were converted due to difficulties encountered intraoperatively which is higher than the conversion rate of patients found in other reports which is 5.9%, 12 due to difficult anatomy (6.55%) 8 due to the discovery of adhesions (4.37%) and one patient's operations were converted due to common bile duct injuries (0.54%). 12 Acute inflammation around Calot's triangle makes the tissue friable and difficult to grasp. Dissection in such conditions leads to excessive bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced age was evaluated as a risk factor for difficult cholecystectomy (19,20). Studies suggested that LC was safe, did not increase complication rates, shortened the time of hospitalization, and was associated with a marked improvement in the quality of life for the elderly.…”
mentioning
confidence: 99%
“…Sakpal et al have stated that male patients >50 years of age and operated by low-volume surgeons have a higher rate of conversion. [12] In our study, obtained lower rate of conversion could be associated with all of these factors since most of our patients were female, the median age was 51 years , and all operations were performed by our experienced senior staff. In recent years, drain usage in surgery has been a commonly queried issue and it has been shown that prophylactic drain insertion adds no benefits even in complicated acute cholecystitis.…”
Section: Discussionmentioning
confidence: 96%
“…Various conversion rates have been reported in the literature, ranging from 4.9% to 29%. [12][13][14] With limited number of patients, our conversion rates were 2.1% and 3%, in chronic and acute cholecystitis, respectively. Although there were high conversion rates in some studies, recent and large reports have shown marked decrease over time.…”
Section: Discussionmentioning
confidence: 99%